Effect of Radish (Raphanus Sativus L.) Height on Natural Drying Characteristics and Mathematical Modeling - Haryanto, Bode; Claudya Elysabeth Simamora; Vikram Alexander; Richard Felix Jonathan Sinaga (Science & Technology Asia, 2024)
The fresh vegetable radish (Raphanus sativus L.) is perishable due to its high water content of about 87%, and radishes spoil quickly. This study aimed to study the impact of variations in radish weight on drying time, ascertain the characteristics of radish drying with natural drying, and determine the mathematical model of radish drying. The measurements of the drying samples determined in this study for the radishes are a length of 4 cm, a width of 2 cm, and height of 0.5 cm, 1.0 cm, and 1.5 cm, which will be dried under sunlight or not exposed to sunlight. The results showed that the radish height of 0.5 cm responds to the decrease in mass during outdoor drying. The explanation of the radish drying process is arrived at by matching the research data of three model equations, namely the Newton, Page, and Henderson-Pabis models. Furthermore, the suitability was determined by the coefficient of determination (𝑅2). The Page model was the most suitable drying model to explain radish drying. The changes in the characteristics of the radish before and after the drying process were detected using a scanning electron microscope.